2023
DOI: 10.3847/2041-8213/ace03a
|View full text |Cite
|
Sign up to set email alerts
|

Jetted and Turbulent Stellar Deaths: New LVK-detectable Gravitational-wave Sources

Abstract: Upcoming LIGO–Virgo–KAGRA (LVK) observing runs are expected to detect a variety of inspiralling gravitational-wave (GW) events that come from black hole and neutron star binary mergers. Detection of noninspiral GW sources is also anticipated. We report the discovery of a new class of noninspiral GW sources—the end states of massive stars—that can produce the brightest simulated stochastic GW burst signal in the LVK bands known to date, and could be detectable in LVK run A+. Some dying massive stars launch bipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Each accretion disk of an episode has a mass of ≈10 −2 M e and the jets of each episode carry ≈10% of this mass. Although the asymmetrical accretion process onto the NS accompanied by rotation can lead to gravitational wave emission (e.g., Dall'Osso & Stella 2007;Menon et al 2023), based on the results of Gottlieb et al (2023), I expect that in the JJEM the jittering jets are the major source of gravitational waves.…”
Section: The Assumptions Of the Toy Modelmentioning
confidence: 99%
“…Each accretion disk of an episode has a mass of ≈10 −2 M e and the jets of each episode carry ≈10% of this mass. Although the asymmetrical accretion process onto the NS accompanied by rotation can lead to gravitational wave emission (e.g., Dall'Osso & Stella 2007;Menon et al 2023), based on the results of Gottlieb et al (2023), I expect that in the JJEM the jittering jets are the major source of gravitational waves.…”
Section: The Assumptions Of the Toy Modelmentioning
confidence: 99%
“…The goal of this exploratory study is to estimate the expected contribution of jittering jets to gravitational wave emission from CCSNe. The motivation for this studyresults from recent studies that support the jittering jets explosion mechanism (JJEM) of CCSNe (e.g., Soker 2022aSoker , 2022cSoker , 2023bShishkin & Soker 2023), and the very recent study by Gottlieb et al (2023) who found that the turbulent cocoons that energetic relativistic jets form can be a strong source of gravitational waves. A cocoon is the convective bubble that a jet inflates, even if not relativistic (e.g., Izzo et al 2019), and is filled with the shocked jet's material and the shocked ambient material.…”
Section: Introductionmentioning
confidence: 99%
“…A cocoon is the convective bubble that a jet inflates, even if not relativistic (e.g., Izzo et al 2019), and is filled with the shocked jet's material and the shocked ambient material. Gottlieb et al (2023) simulated relativistic and very energetic jets, ≈10 52 -10 53 erg, that are relevant to rare CCSNe where the pre-explosion core is rapidly rotating and the collapsing core is likely to form a black hole. There are many studies of such rare CCSNe that have fixed-axis jets; some do not consider gravitational waves from jets (e.g., Khokhlov et al 1999;Aloy et al 2000;Maeda et al 2012;López-Cámara et al 2013;Bromberg & Tchekhovskoy 2016;Nishimura et al 2017;Wang et al 2019;Grimmett et al 2021;Gottlieb et al 2022;Perley et al 2022;Urrutia et al 2023a;Obergaulinger & Reichert 2023), while others do (e.g., analytically Segalis & Ori 2001;Du et al 2018;Yu 2020;Leiderschneider &Piran 2021 andnumerically Urrutia et al 2023b;Gottlieb et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The jet wobbling is caused by the spontaneous tilt of the disk, induced by the stochastic torques applied to the disk by infalling gas. Consequently, a given observer will only see a fraction of the jet energy, so that the observed jet energy is in fact an order of magnitude lower than the true jet energy (Gottlieb et al 2023). In such cases, the total GRB jet energy is…”
mentioning
confidence: 99%